A robotized handheld smart tool for orthopedic surgery. Issue 5 (5th June 2021) - Hung, Shuo‐Suei; Hsu, Alex Shao‐Feng; Ho, Tsung‐Han; Chi, Chau‐Hwa; Yen, Ping‐Lang
Abstract: Background: Handheld surgical robots offer functionalities, such as active guidance, tremor suppression and force reflection, for surgeons to enhance their skill in manipulating surgical tools during medical intervention. In orthopedic surgery, the robot additionally has to offer sufficient rigidity and power for bone machining. The size and weight of the mechanical design, together with the control behaviour associated with involuntary hand motion, navigation and reflected force to the human, all influence the overall performance of an orthopedic handheld robot. Methods: The paper proposes a miniature and compact design for an embedded robot, which is a similar weight as a handpiece. Then, a shared controller is proposed to address the coupling among involuntary and voluntary hand motions, robot navigation, tool feedback forces and force artefacts from actuation. Results: The handheld robot is able to stabilize the drill positioning by removing involuntary tremors as well as reduce force artefacts from motor actuation in experiments involving pedicle tunnelling on a porcine spine. Conclusion: The paper has successfully realized a compact handheld orthopedic robot which provides high performance of usability, tremor suppression and force reflection for bone drilling.